Characterization and comparison of the aroma-active compounds on different grades of sesame-flavor Baijiu by headspace solid-phase microextraction and gas chromatography-olfactometry-mass spectrometry - Dan Qin; Jiawen Duan; Hehe Li; Fuping Zheng; Huan Cheng; Xingqian Ye; Baoguo Sun (Food Science and Human Wellness)
This study investigated the aroma-active compounds and compared the differences of three different grades of sesame-flavor Baijiu by headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography-olfactometry-mass spectrometry (GC-O-MS). A total of 54 aroma-active compounds were detected. Principal component analysis showed that JZ1, JZ2, and JZ3 were well separated from each other. JZ1 as the premium-grade Baijiu had the highest aroma intensities, concentrations. According to aroma intensities and concentrations, dimethyl trisulﬁde, butanoic acid, phenylacetaldehyde, 2-furylmethanethiol, ethyl hexanoate, 2,6-dimethylpyrazine, etc. could be potentially applied as volatile makers to distinguish the three different grades of sesame-flavor Baijiu as their significant difference (P < 0.05) in three Baijiu samples. Roasted aroma had the significant difference (P < 0.05) in three sample base on aroma profiles. Meanwhile, 2-furylmethanethiol, 2,6-dimethylpyrazine were related to the roasted aroma, they may be had a significant contribution to the differences of three different grades of sesame-flavor Baijiu. This study has provided a comprehensive understanding of the differences of three different grades of sesame-flavor Baijiu.